PENERAPAN MEDIA VIDEO PADA PEMBELAJARAN DARING DALAM UPAYA MENINGKATKAN HASIL BELAJAR PRAKARYA KELAS 8 SMP NEGERI 10 MALANG - RENY SETYOWATI PRODJO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
This research is a Classroom Action Research (CAR) in the form of the application of video media in online learning with the aim of improving the learning outcomes of students in class 8C-D study groups in the even semester of SMP Negeri 10 Malang in the academic year 2020-2021 which is carried out in two cycles and each cycle consists of planning, implementing, observing, and reflecting. The research subjects were study group students who chose the Processing aspect of class 8C-D SMP Negeri 10 Malang with the number of students in this study 30 students consisting of 14 students in class 8C and 16 students in class 8D who joined in one study group, namely class Processing Crafts where this class is a study group of students who choose the processing aspect in the Craft subject. The results showed that the application of video media in online learning could improve the learning outcomes of Crafts learning for students in the 8C-D class even semester of SMP Negeri 10 Malang. Judging from the beginning of the research at the pre-cycle stage, the learning outcomes of students who completed the KKM were 17 students (56.7%), and 13 students (43.3%) who had not yet completed. In the first cycle there are 25 students (83.3%) who have completed and 5 students (16.7%) have not completed, and in the second cycle there are 28 students (93.3%) who have completed and there are 2 students (6.7%) that have not been completed. From the increase in learning outcomes, this class action research was only carried out until the second cycle stage because it had reached the classical completeness criteria, namely 85% of the total number of students who had completed learning and were declared successful in improving the craft learning outcomes for students in the 8C-D semester study group. Even SMP Negeri 10 Malang for the academic year 2020/2021. ABSTRAKPenelitian ini merupakan Penelitian Tindakan Kelas (PTK) berupa penerapan media video pada pembelajaran daring dengan tujuan meningkatkan hasil belajar Prakarya peserta didik kelompok belajar kelas 8C-D pada semester genap SMP Negeri 10 Malang tahun pelajaran 2020-2021 yang dilaksanakan dengan dua siklus dan setiap siklus tediri dari perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian pada peserta didik kelompok belajar yang memilih aspek Pengolahan kelas 8C-D SMP Negeri 10 Malang dengan jumlah peserta didik dalam penelitian ini 30 peserta didik terdiri dari 14 peserta didik kelas 8C dan 16 peserta didik kelas 8D yang tergabung dalam satu kelompok belajar yakni kelas Prakarya Pengolahan dimana satu kelas ini merupakan satu kelompok belajar peserta didik yang memilih aspek pengolahan dalam mata pelajaran Prakarya. Hasil penelitian menunjukkan bahwa penerapan dengan media video pada pembelajaran daring dapat meningkatkan hasil belajar Prakarya pada peserta didik kelompok belajar kelas 8C-D Semester Genap SMP Negeri 10 Malang. Dilihat dari awal penelitian pada tahap Pra siklus hasil belajar peserta didik yang tuntas KKM 17 peserta didik (56,7%), dan 13 peserta didik (43,3%) yang belum tuntas. Pada siklus I terdapat 25 peserta didik (83,3%) yang tuntas dan 5 peserta didik (16,7%) yang belum tuntas, dan pada siklus II terdapat 28 peserta didik (93,3%) yang tuntas dan terdapat 2 peserta didik (6,7%) yang belum tuntas. Dari peningkatan hasil belajar tersebut penelitian tindakan kelas ini hanya dilakukan sampai tahap siklus II karena telah mencapai kriteria ketuntasan klasikal yaitu ? 85% dari jumlah seluruh peserta didik tuntas belajar dan dinyatakan berhasil untuk meningkatkan hasil belajar Prakarya pada peserta didik kelompok belajar kelas 8C-D semester Genap SMP Negeri 10 Malang Tahun Pelajaran 2020/2021.